A Comparative Study on Poverty Alleviation Between Moslem and Non Moslem Populated Countries - Hudaifah, Ahmad; Ajija, Shochrul Rohmatul (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2017)
The paper attempts to explore the problems and roots of poverty, the poverty alleviation progress, programs and policies between selected Moslem populated-countries in Asia and selected non-Moslem populated-countries in Latin America. By conducting comparative analysis on statistical data, literature surveys, several journals, official reports and reliable research findings, all sources have been examined to construct comprehensive findings in the present article. Three important aspects are concluded. Firstly, by definition, a person who earns below 2,00 USD per day is considered “poor” according to the World Bank, and they are mostly living in rural areas and suburban slums. Second, poverty alleviation efforts in both particular groups of countries have resulted in a better outcome, whereby the number of poor decreased gradually according to statistical data reported by the World Bank. Other economic indicators such as GNI per capita and income inequality graphic have shown better patterns. Third, there have been different strategic policies and programs implemented between the two groups of countries. Islamic economic notions such as zakah, infaq, and sadaqah play a very significant role in Moslem populated countries, on the other hand, non Moslem populated countries tend to create more radical and creative strategies such as agendas of land reform and tourism industry development. DOI: 10.15408/aiqv9i1.3222